Inorganic Reactions Self‐organize Life‐like Microstructures Far from Equilibrium. Issue 6 (6th April 2018) - Knoll, Pamela; Steinbock, Oliver
Abstract: A fundamental problem in chemistry is the nontrivial extension of molecular complexity to macroscopic length scales. The exploration of such concepts offers profound insights into the hierarchical organization of living matter and promises a novel engineering paradigm under which materials and devices are grown biomimetically far from the thermodynamic equilibrium. Inorganic microstructures called biomorphs are an ideal model system to develop such approaches. They are polycrystalline nanorod assemblies that form in basic solution from alkaline‐earth metal ions, silicate, and carbonate. Biomorphs range in size from tens of micrometers to millimeters and form over several hours under simple experimental settings. Their noneuhedral, life‐like shapes include surprising leafs, helices, funnels, urns, and coral‐shaped motifs. Here we review the current understanding of biomorphs, highlight links to nonlinear chemical dynamics, and discuss applications in materials science and astrobiology. Abstract :